Smart-Glass Glazing using Arduino and Android Application - Jabbar, Mohammed M.; Zaki, Salim M (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The parts of buildings most susceptible to light and heat are the windows, which are necessary for basic cooling and heating. A huge amount of electrical energy is used to power air conditioners to adjust the inside temperature of residential buildings, while appropriate glazing techniques and materials can be used to reduce energy consumption. There are classic techniques used for tinting glass in buildings and cars, but they all continue to use fixed techniques with one degree of glazing. Users cannot adjust the glazing of these glasses in response to the intensity of sunlight either automatically or by hand. In this research, a modern technique is proposed to allow users to automatically control a glass’s glazing through sensors and Android application with a microcontroller. Arduino microcontroller is used along with a special film polymer dispersed liquid crystals (PDLC) material coating the glasses to enable tinting. The results show adjustable levels of tinting with PDLC film being enabled.